1976
DOI: 10.1002/art.1780190503
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of patients with serum antibodies to extractable nuclear antigens

Abstract: A distinguishing feature of the mixed connective tissue disease (MCTD) syndrome is the presence in the serum of antibody in high titer to ribonucleoprotein (RNP). To determine whether this was an exclusive observation, a large rheumatic disease population was surveyed for the presence of antibody in high titer to extractable nuclear antigens (ENA) including RNP. Of 650 sera examined, 440 (from 240 patients) had antinuclear antibody. Only 39 patients had serum antibody to ENA in titers ≧ 1:200 dilution. In 16 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
1

Year Published

1977
1977
1994
1994

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(21 citation statements)
references
References 13 publications
5
15
1
Order By: Relevance
“…This further adds to evidence reported from several American centres (Bennett and Spargo, 1977;Farber and Bole, 1975;Fuller et al, 1977;Hench, Edgington and Tan, 1975;Leibfarth, McChesney and Persellin, 1975;Tan, Northway and Pinnas, 1973;Venkateswara et al, 1976) and recently from Paris (Gaudreau et al, 1978) that renal involvement does occur in MCTD. The case reported here is all the more unusual as, of those reported cases, only that by Fuller et al (1977) was definitely associated with hypocomplementaemia, the usual finding being normal or raised complement levels.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This further adds to evidence reported from several American centres (Bennett and Spargo, 1977;Farber and Bole, 1975;Fuller et al, 1977;Hench, Edgington and Tan, 1975;Leibfarth, McChesney and Persellin, 1975;Tan, Northway and Pinnas, 1973;Venkateswara et al, 1976) and recently from Paris (Gaudreau et al, 1978) that renal involvement does occur in MCTD. The case reported here is all the more unusual as, of those reported cases, only that by Fuller et al (1977) was definitely associated with hypocomplementaemia, the usual finding being normal or raised complement levels.…”
Section: Discussionsupporting
confidence: 73%
“…Of those reported membranous glomerulonephritis was recognized in 3 cases by Bennett and Spargo (1977) and one case each by Hench et al (1975) andFuller et al (1977) although the latter also contained some focal mesangial proliferative changes. Venkateswara et al (1976) reported a case with focal mesangial proliferative changes, and single cases of Leibfarth et al (1975) and Tan et al (1973) revealed focal proliferative and proliferative glomerulonephritic changes respectively. All these cases had glomerular deposits of complement and immunoglobulin.…”
Section: Discussionmentioning
confidence: 99%
“…The present study would suggest that under appropriate conditions involvement of the properdin system may further result in severe and even fatal disease, although clearly this represents an unusual experience. It is of interest that the predominant antinuclear antibody detected was anti-RNP, which paradoxically has been described as modulating or protecting against glomerular injury induced by antibodies of DNA or Sm specificity (50)(51)(52). Whether anti-RNP can activate the alternative pathway and/or mediate disease preferentially when C2 is deficient is not yet known.…”
Section: Discussionmentioning
confidence: 99%
“…The demographic and clinical features of these 81 patients (Tables 2 and 4) were comparable to those noted in previous large series of SLE patients (6,10,11,13,14), suggesting that our study population was not skewed toward factors associated with milder disease or overlap features. We did not select individuals solely on the basis of certain antibody profiles, as has been done by others (17)(18)(19)22,23,25,26) in studying the effects of antiENA antibody. The subsets of the overall SLE patient group were defined solely on the presence or absence of antibodies to ENA and its RNP component, irrespective of clinical features or presence of antibody to deoxyribonucleic acid (DNA).…”
Section: Discussionmentioning
confidence: 99%